C.P.A. COMMERCIAL LAW EXAMINATIONS. - Teevan, John C. (The Accounting Review, 1936)
Abstract The article focuses on the Certified Public Accountants (CPA) commercial law examinations. To find a place in their field and to achieve any degree of success therein, accountants find it necessary to become a CPA. The usual qualifications for candidacy for the CPA examination are that the examinee be 21 years of age, have had a high school education or the equivalent thereof, and a certain number of years of practical experience in accounting. The subjects in which the CPA candidate is examined are: theory of accounting, practical accounting, auditing and commercial law. The law examination, thus, forms 25% of the total examination. About ten other states use the examinations prepared by the American Society of Certified Public Accountants. The law divisions of these examinations contains about thirty-six questions, from which the states using them choose the number and kind they desire. Thus, these examinations play a vital role in the international accounting arena in the corporate world.